2017
DOI: 10.1515/pielxxiw-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Review of studies concerning job performance of nursing staff

Abstract: STRESZCZENIEPRZEGLĄD BADAŃ NAD WYDAJNOŚCIĄ PRACY PIELĘGNIAREK Wprowadzenie. Wydajność pracy, czyli całkowita wartość zachowań oczekiwanych od pracowników w czasie oceny przeprowadzonej w ustalonym czasie. W podstawowym i dychotomicznym podziale odnosi się wydajność do płaszczyzny zachowań pracowniczych (behawioralny) oraz wyników ich pracy. Dodatkowo badacze wyróżniają: wydajność zadaniową, wydajność kontekstową oraz wydajność adaptacyjną. Wnioski. Tematyką wydajności pracy pielęgniarek zajmowano się w badania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The WAI tool makes it possible to quantitatively present subjective assessments of current and future workloads, physical and mental capabilities to overcome them, and health and its impact on work ability (Makowiec-Dąbrowska et al, 2008). Szara et al (2017) and Rostamabadi et al (2017) (Abbasi et al, 2017;Silva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WAI tool makes it possible to quantitatively present subjective assessments of current and future workloads, physical and mental capabilities to overcome them, and health and its impact on work ability (Makowiec-Dąbrowska et al, 2008). Szara et al (2017) and Rostamabadi et al (2017) (Abbasi et al, 2017;Silva et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Szara et al. (2017) and Rostamabadi et al. (2017) emphasize that the efficiency of a nurse's work is a combination of many factors and should thus be viewed in a multidimensional way.…”
Section: Discussionmentioning
confidence: 99%
“…The topic of nurse productivity is the subject of a study reviewed by Szara et al [50]. The review of studies showed that this topic is little recognized in the national literature, and based on the available world literature (finally 33 articles included in the review), the following conclusions were presented: nurse productivity depends on organizational culture, leadership, intensity of care, patient education, planning and evaluation of nursing care outcomes, interpersonal relationships, professional development of the employee, personal characteristics of the employee, shift work, stress levels, and social support.…”
Section: Economic and Social Consequences Of Inadequate Carementioning
confidence: 99%